Phobos 2/ASPERA data revisited: Planetary ion escape rate from Mars near the 1989 solar maximum. Issue 3 (13th February 2013) - Ramstad, Robin; Futaana, Yoshifumi; Barabash, Stas; Nilsson, Hans; Martin del Campo B, Sergio; Lundin, Rickard; Schwingenschuh, Konrad
Abstract [1] Insights about the near‐Mars space environment from Mars Express observations have motivated a revisit of the Phobos 2/ASPERA ion data from 1989. We have expanded the analysis to now include all usable heavy ion (O+, O<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg371m8mj5" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2+</alternatives>, CO<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgg371m8mg2" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />2+</alternatives>) measurements from the circular orbits of Phobos 2. Phobos 2/ASPERA ion fluxes in the Martian tail are compared with previous results obtained by the instruments on Phobos 2. Further validation of the measurement results is obtained by comparing IMP‐8 and Phobos 2/ASPERA solar wind ion fluxes, taking into account the time lag between Earth and Mars. Heavy ion flux measurements from 18 circular equatorial orbits around Mars are bin‐averaged to a grid, using the MSE (electric field) frame of reference. The binned data are subsequently integrated to determine the total escape rate of planetary ions. From this we derive a total planetary heavy ion escape rate of (2–3) × 1025 s−1 from Mars for the 1989 solar maximum.